Pengaruh Motivasi Kerja Guru dan Fasilitas Belajar terhadap Kinerja Guru SMA Negeri 11 Padang - Fitrianti Fitrianti; Febri Susanti (JUMBIWIRA : Jurnal Manajemen Bisnis Kewirausahaan, 2025)
This study aims to examine the influence of teacher work motivation and learning facilities on teacher performance at SMA Negeri 11 Padang. The research employed a quantitative approach, with a population consisting of all 47 teachers at the school. The sampling technique used was total sampling, in which the entire population was taken as the sample. Primary data were collected through structured questionnaires distributed to the respondents, and the analysis was carried out using SPSS Software Version 24. The results of this study indicate that teacher work motivation has a positive and significant effect on teacher performance. Similarly, the availability and quality of learning facilities also have a positive and significant effect on teacher performance. These findings suggest that improving teacher motivation and providing adequate learning facilities are crucial factors in supporting the achievement of better performance outcomes. In addition, the study emphasizes that both motivation and facilities complement each other in shaping teacher productivity and professionalism. The implication of this research is that schools should give serious attention to strengthening motivational factors as well as ensuring the provision of appropriate facilities in order to improve the overall quality of education delivery.